PERENCANAAN JADWAL INDUK PRODUKSI DENGAN MENGGUNAKAN LINIER PROGRAMING PADA PERUSAHAAN PUPUK ORGANIK âXYZâ - ., Marcahyono (DINAMIKA DOTCOM, 2013)
Consumer demand for an fluctuations tastes of the market is following the constraints in planning and scheduling because the effect on production costs and inventory costs incurred. Organic Fertilizer company